The first complete mitochondrial genome sequence of the leucosiid crab Pyrhila pisum (Arthropoda, Decapoda, Leucosiidae). Issue 2 (12th December 2017) - Park, Yeong-Jun; Park, Chang Eon; Jung, Byung Kwon; Ibal, Jerald Conrad; Jung, YeonGyun; Hong, Sung-Jun; Park, Gun-Seok; Lee, Seok Hyun; Sook Ko, Hyun; Shin, Jae-Ho
Abstract: Pyrhila pisum is known as leucosiid crab. So far, there is no study about whole mitochondrial genome in Leucosiidae family. Here, we report first the complete sequence of the mitochondrial genome from P. pisum, which is composed of 15, 516 base pair encoding 13 protein-coding genes, 22 transfer RNAs, two ribosomal RNAs, and A + T-rich region. The nucleotide composition of P. pisum was G + C: 25.5%, A + T: 74.5%, with a strong AT bias. In phylogenetic analysis using whole mitogenome, it was figured out that P. pisum was closely related to Sesarma neglectum but their family is different.